Pemodelan Pola Perambatan Gelombang Kalsium Pada Jaringan Astrocyte Dengan Simulator Brian2 - Hafizhoh, Itsnainiyah; Yuniati, Anis (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2020)
Calcium wave propagation pattern modeling has been successfully carried out in astrocyte network using Brian2 simulator. The astrocyte model is defined by the Li-Rinzel equation which involves the IP3Rs (q) activation fraction. IP3Rs activation fraction parameter (q) affects the value of calcium concentration in astrocytes. The connection between astrocyte is in the form of Gap-Junction Channels (GJCs). The variation in this modeling is the number of astrocyte cells stimulated by external currents in the astrocyte network being modeled. The modeling results show that the IP3Rs (q) activation fraction can affect the propagation of calcium waves in astrocytes through activation of IP3 receptors